Has εὐβίοτος in Aristotle’s Historia Animalium ix Been Mistranslated? - Chelsea Harry (Revista de Filosofia Antiga)
The term, εὐβίοτος, “living well” and its cognates appear in Aristotle’s observations of bird life in Historia Animalium ix. This research note compares the way Aristotle’s term was rendered in Greek, Latin, and Arabic manuscripts, and in modern and contemporary translations in English, French, and German, to argue that it has been rendered infelicitously, beginning with the 15th-century humanist translators, George of Trebizond and Theodore Gaza. The liberties taken in over-interpreting Aristotle’s term might have obscured what he was trying to communicate about bird capabilities.